Changes in coronary heart disease risk profiles of HIV patients in Zimbabwe over 9 months: a follow-up study - Zhou DT (Dove Medical Press, 2016)
Danai Tavonga Zhou,1,2 Olav Oektedalen,3 Sandra Shawarira-Bote,4 Babill Stray-Pedersen5 1Department of Medical Laboratory Sciences, College of Health Sciences, University of Zimbabwe, Avondale, Harare, Zimbabwe; 2Institute of Clinical Medicine, University of Oslo, 3Department of Infectious Diseases, Oslo University Hospital, Oslo, Norway; 4Newlands Clinic, Harare, Zimbabwe; 5Institute of Clinical Medicine, University in Oslo and Womens Clinic, Oslo University Hospital, Oslo, Norway Abstract: Dyslipidemia, hypertension, inflammation, and coronary heart disease (CHD) are adverse events in human immunodeficiency virus (HIV)-infected patients even if they are receiving antiretroviral therapy (ART). Yet, data on CHD risk induced by HIV or ART in sub-Saharan Africa are limited. The aim of this longitudinal study was to describe changes in CHD risk profiles measured by lipids, inflammatory markers, and Framingham scores among HIV-positive patients previously reported from Harare, Zimbabwe. Patients were grouped into ART-experienced patients (n=147) and ART-naïve patients (n=23) and followed up for 9 months. Generalized least squares random-effects modeling was applied to explain changes in total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein, TC/HDL ratio, myeloperoxidase, highly sensitive C-reactive protein, and Framingham scores over the 9-month period. Independent variables included age, sex, monthly earning, body mass index, systolic blood pressure (SBP), diastolic blood pressure, duration of HIV diagnosis, duration of ART, viral load, and CD4 count. In ART-experienced patients, there was a substantial decrease in TC over time, ART-negative patients showed a significant increase in TC and HDL over time, and the increase in TC was associated with high viral load and low duration of HIV diagnosis, while increase in HDL was associated with young age, low body mass index, and low SBP. Framingham risk scores increased with time in ART-positive patients, and the change was positively correlated with age, sex, high SBP, and low HDL. There was no association between calculated CHD risk (TC/HDL ratio or Framingham score) and changes in levels of inflammatory markers (myeloperoxidase and highly sensitive C-reactive protein) in any of the patient groups. In conclusion, ART-experienced HIV-positive patients show changes in lipid values over time that makes it necessary to include lipid monitoring in order to reduce any risk of long-term CHD. Keywords: ART, CHD, cohort, Framingham, HIV